Resident-Level Predictors of Dementia Pharmacotherapy at Long-Term Care Admission: The Impact of Different Drug Reimbursement Policies in Ontario and Saskatchewan: Prédicteurs de la pharmacothérapie de la démence au niveau des résidents lors de l’hospitalisation dans des soins de longue durée : l’impact de différentes politiques de remboursement des médicaments en Ontario et en Saskatchewan - Maclagan, Laura C. (Can J Psychiatry, 2020)
OBJECTIVES: Cholinesterase inhibitors (ChEIs) and memantine are approved for Alzheimer disease in Canada. Regional drug reimbursement policies are associated with cross-provincial variation in ChEI use, but it is unclear how these policies influence predictors of use. Using standardized data from two provinces with differing policies, we compared resident-level characteristics associated with dementia pharmacotherapy at long-term care (LTC) admission. METHODS: Using linked clinical and administrative databases, we examined characteristics associated with dementia pharmacotherapy use among residents with dementia and/or significant cognitive impairment admitted to LTC facilities in Saskatchewan (more restrictive reimbursement policies; n = 10,599) and Ontario (less restrictive; n = 93,331) between April 1, 2009, and March 31, 2015. Multivariable logistic regression models were utilized to assess resident demographic, functional, and clinical characteristics associated with dementia pharmacotherapy. RESULTS: On admission, 8.1% of Saskatchewan residents were receiving dementia pharmacotherapy compared to 33.2% in Ontario. In both provinces, residents with severe cognitive impairment, aggressive behaviors, and recent antipsychotic use were more likely to receive dementia pharmacotherapy; while those who were unmarried, admitted in later years, had a greater degree of frailty, and recent hospitalizations were less likely. The direction of the association for older age, rural residency, medication number, and anticholinergic therapy differed between provinces. CONCLUSIONS: While more restrictive criteria for dementia pharmacotherapy coverage in Saskatchewan resulted in fewer residents entering LTC on dementia pharmacotherapy, there were relatively few differences in the factors associated with use across provinces. Longitudinal studies are needed to assess how differences in prevalence and characteristics associated with use impact patient outcomes.